PENGARUH PAPARAN LINEAR ALKALYBENZEN SULFONAT (LAS) TERHADAP KADAR PROTEIN TOTAL PADA IKAN NILA (Oreochromis niloticus) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Ayu Putri Lestari; Tuti Alawiyah; Nur Hidayah (Jurnal Medical Laboratory, 2022)
Tilapia is a source of protein that is healthy and low in fat. Tilapia is a source of protein that is healthy and low in fat. Animal protein is found in fish, one of which is tilapia which has a protein content of more than 16.05%. One of the causes of protein denaturation is detergent. Razmi's research results, 2021 measuring the levels of laundry waste in Martapura river water in Sungai Lulut Village obtained concentrations at a distance of 100 meters of 3.4 mg/L, a distance of 200 meters of 2.4 mg/L and a distance of 300 meters of 1.6 mg/L. To determine the effect of exposure to Linear Alkalybenzen Sulfonate (LAS) on total protein levels in tilapia in the Martapura River and the effect of differences in time intervals of exposure to Linear Alkalybenzen Sulfonate (LAS) on total protein levels in tilapia in the Martapura River. This research uses Pre Experimental with Post Test Only Control Group Design approach. The test method was carried out qualitatively and quantitatively. The qualitative test method was carried out by the biuret test while the quantitative test method saw the difference in the time interval of exposure to Linear Alkalybenzen Sulfonate (LAS) on the total protein content of tilapia using Visible Spectrophotometric instruments. Data analysis using One-Way ANOVA. Based on the qualitative analysis, all samples were positive in the biuret test. The results of the quantitative analysis obtained were a decrease in total protein levels at intervals of 0.3,6,9 hours with an average control at 3 hours 2.26%, 3 hours to 6 hours 4.49%, and 6 hours to 9 hours. 4.5%. 501.64 ppm. The administration of LAS with different intervals of exposure (control, 3 hours, 6 hours, 9 hours) showed a significant effect on the total protein content of tilapia, namely a decrease in the total protein content.